Walk on the wild side: SIV infection in African non-human primate hosts—from the field to the laboratory - Jasinska, Anna J.; Apetrei, Cristian; Pandrea, Ivona (Frontiers in Immunology, 2023)
HIV emerged following cross-species transmissions of simian immunodeficiency viruses (SIVs) that naturally infect nonhuman primates (NHPs) from Africa. While HIV replication and CD4+ T-cell depletion lead to increased gut permeability, microbial translocation, chronic immune activation and inflammation, the natural hosts of SIVs generally avoid these deleterious consequences when infected with their species-specific SIVs, and do not progress to AIDS despite persistent lifelong high viremia, due to long-term coevolution with their SIV pathogens. The benign course of natural SIV infection in natural hosts is in stark contrast to experimental SIV infection of macaques, which progresses to simian AIDS. The mechanisms of nonpathogenic SIV infections are studied mainly in African green monkeys, sooty mangabeys and mandrills, while progressing SIV infection is experimentally modeled in macaques: rhesus macaques, pigtailed macaques and cynomolgus macaques. Here, we will focus on the distinctive features of natural SIV infection, particularly: (1) the superior healing properties of intestinal mucosa, which enable them to maintain the integrity of the gut barrier and prevent microbial translocation, thus avoiding excessive/pathologic immune activation and inflammation usually perpetrated by the leaking of the microbial products into the circulation; (2) the gut microbiome, a disruption of which is an important factor in some inflammatory diseases, yet not completely understood in the course of lentiviral infection; (3) cell population shifts resulting in target cell restriction (downregulation of CD4 or CCR5 surface molecules which bind to SIV), control of viral replication in the lymph nodes (expansion of natural killer cells), and anti-inflammatory effects in the gut (NKG2a/c+ CD8+ T-cells), and (4) genes and biological pathways that can shape genetic adaptations to viral pathogens and are associated with the nonpathogenic outcome of the natural SIV infection. Deciphering the protective mechanisms against the SIV disease progression to immunodeficiency, which were established through a long-term coevolution between the natural hosts and their species-specific SIVs may stimulate development of novel therapeutic interventions, such as drugs that can control gut inflammation, enhance gut healing capacities, or modulate gut microbiome. These developments can go beyond HIV infection and open large avenues for correcting gut damage that is common to so many diseases.